Association of Mutations in the NS5A-PKRBD Region and IFNL4 Genotypes with Hepatitis C Interferon Responsiveness and its Functional and Structural Analysis - Hashempour, Tayebeh; Dehghani, Behzad; Mousavi, Zahra; Akbari, Tahereh; Hasanshahi, Zahra; Moayedi, Javad; Yahaghi, Maryam; Davarpanah, Mohammad A. (Current Proteomics, 2021)
Background: The cellular antiviral responses induced by interferons require some cellular protein kinase for its activation. Evidence indicated that a number of Hepatitis C Virus (HCV) proteins can repress double-stranded (ds) RNA-dependent Protein Kinase (PKR) function and help HCV to escape. However, the reports are controversial, some researchers have suggested that a region in Nonstructural 5A (NS5A) gene called Protein Kinase R-Binding Domain (PKR-BD) is associated with HCV sensitivity to the antiviral effects of Interferon (IFN). In addition, the other factor that might be associated with response to PEGylated-IFNα (Peg-IFNα) and Ribavirin (RBV) combination therapy, is IFNL4 genotypes. Objective: The aim of this study was to investigate the association between amino acid (aa) substitutions in the NS5A region and the IFNL4 genotypes in two Single Nucleotide Polymorphism (SNP) (rs8099917. rs12979860) in patients with HCV genotypes 1a and 3a. We also examined their response to combination therapy and the effect of these mutations on the function and structure of PKR-BD. Methods: Eighty-six patients with hepatitis C were recruited and follow-up for 6 months. Several tests, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), viral load, IFNL4 genotyping, and PKR-BD sequencing were performed. Using several well-known and trustworthy bioinformatics tools, sequences were analyzed to define physio-chemical properties, structural features, immune epitopes and protein-protein interaction. Results: Of the 86 patients, 65.1% had high viral load at baseline, 64% had CT genotype for rs12979860 and 57% had GT genotype for rs8099917. Several aa residues changes were found in the PKR-BD region. We could not find any link between mutations in the PKR-BD region and different genotypes of IFNL4 in response to antiviral therapy. Regardless of pI, PKR-BD 1a and 3a showed similar physio-chemical properties, and 2 phosphorylation sites and one glycosylation site were estimated for both PKR-BD 1a and 3a. Trustworthy software were employed in order to predict B-cell epitopes, 3 regions (6-17, 26-32, 34-41) were found for both proteins, indicating a huge potential of PKR-BD protein to induce humoral immune system. Docking analysis determined non-responder sequences in both 1a and 3a genotypes to have higher energy value and are more compatible with PKR. Conclusion: To sum up, our results could not determine any significant relationship between mutations of PKR-BD and genotypes of IFNL4 with other factors; ALT, AST, viral load. However, docking results showed strengthened interaction between PKR-BD and PKR in non-responders that could have a momentous impact on the illness severity.
Keywords: PKR-BD